Destruction, Policy, and the Evolving Consequences of Washington, DC’s 1968 Civil Disturbance - Brooks, Leah; Rose, Jonathan; Veuger, Stan (The Review of Economics and Statistics, 2026)
We study the aftermath of the 1968 Washington, D.C. civil disturbance to illuminate the mechanisms that drive urban redevelopment in the presence of low demand and racial tension. Using a within-block identification strategy, we show that destruction caused lots to remain vacant for the next thirty years and only recently converge in terms of structure value. The city acted to preclude for-profit land owners from leaving land vacant until demand conditions improved by purchasing nearly half of all properties in damaged neighborhoods. Despite this and other steps, the city had limited success in speeding up redevelopment.